Exploring the English Needs of Mechanical Engineering Students in ESP Class: Indonesian University Context - Angga Nafis Akmal; Nur Hidayati; Rafika Rabba Farah (English Learning Innovation (englie), 2020)
English for Specific Purposes in tertiary level puts its importance to Need Analysis (NA) process for syllabus design. This present research is concerned with designing ESP syllabus for Mechanical Engineering students in tertiary level through need analysis. The research aims to identify the immediate needs of the Mechanical Engineering students and design appropriated syllabus based on students’ needs using Target Situation Analysis (TSA) and Present Situation Analysis (PSA). In order to achieve the research’s objectives, a questionnaire was administered to a total 50 respondents. The finding of the research shows that among 4 basic English skills, listening skill emerged as the most important skill that students’ really need, followed by speaking, reading, and writing. Thus, this research suggests that ESP teachers should design more varied activities on listening course that students will have the competence to apply the skills later in future life context.